Pinterest Thrift / Muhammad Khairul Aiman Abdul Rahman … [et al.] - Abdul Rahman, Muhammad Khairul Aiman; Abd Jalil, Akmal Ikhwan; Ahmad Khusairi, Ariff Hakimi; Rafie, Muhammad Ilmam Hasif; Mohamad Fauzi, Muhammad Zulhilmi (2022)
Pinterest Thrift is a home-based business and was the subject for our case study. Our group chose this particular business because of their authenticity in terms of product and affordability. Due to the limitation of distance because it is located too far from us, we opted to interview the owner through a Google Meet session as our medium to communicate virtually and WhatsApp as our medium to message. Introduction, firm information, business model canvas, results and discussion, and conclusion are the five key sections of our case study. The introduction is the first section of our case study. The study's history and goal are explained in this section. We also give a brief introduction to the firm we choose, Pinterest Thrift. The company information section of the research covers the company's history, organisational structure, goods and services, as well as business, marketing, and operational strategies. We go into great detail about Pinterest Thrift, including how they got started, when they were established, and what products and services they offered. The third part of our case study is the business model canvas and the elaboration. In this part, we study more on the Pinterest Thrift’s key partners, key activities, key resources, value proposition, customer relationship, channels, customer segment, cost structure and revenue stream. The findings and discussion section of our case study comes next. According to our results, Pinterest Thrift has few issues that consist of lack of capital, poor marketing strategies, and Improper record keeping. However, we discovered the solution to our results during the conversation. Pinterest Thrift should seek government funding for new company start-ups, develop their marketing tactics, and have proper record keeping. The conclusion is the final section of our case study. We end by discussing what we learnt from our chosen business, Pinterest Thrift, as well as what we learned during the process of completing our case study.